Exploring public cooperation with police: the role of police accountability, police effectiveness, and public trust - Mohamed Abdi, Ahmed-Nor; Hashi, Mohamed Bile (2024)
Public cooperation with the police is crucial because the public acts as the eyes and ears of the police. Moreover, research on public cooperation with the police, including crime-reporting behaviours and willingness to cooperate with law enforcement agencies, remains scarce in post-conflict countries like Somalia. Therefore, this study investigates the roles of perceived police accountability and effectiveness in fostering public cooperation with the police in Somalia via the underlying mechanisms of public trust in the police. Data were collected from a sample of 470 respondents in Mogadishu, Somalia. The analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed model. The study found that police accountability has indirectly and positively impacted public cooperation via public trust in police. Moreover, public trust in police positively and significantly impacts public cooperation with the police. The findings also revealed that police effectiveness, directly and indirectly, impacts public cooperation with the police.